Estudo comparativo entre a membrana de latéx e a membrana de politetraflouretileno (PTFE) na regeneração de defeitos ósseos - Martins, Renato (2008)
This work is a comparative study of the performance of the Natural Latex membrane, derivative of Hevea brasiliensis, and the Polytetrafluorethylene membrane - PTFE as occlusive membranes in Bone Guided Regeneration procedure. The latex is a biocompatible material, with high mechanical resistance and can accelerate the angiogenesis and tissue neoformation. It presents other advantages such as elasticity and the low cost. Initial tests in vivo demonstrated that the Latex membrane is an excellent candidate for Bone Guided Regeneration. However, to evaluate its advantages and disadvantages as an occlusive membrane, a comparative study is necessary. So, in this work, we use the model of craniotomy in rabbits to evaluate the bone regeneration obtained by the use of this membrane in comparison with the use of the PTFE membrane and the control group (without membranes). The choice of the PTFE rely on the fact that its effectiveness had already been proven, to be commercialized and has been used for a long time for this purpose. PTFE is considered as Gold Standard for comparisons with other new materials. In this work the membranes were implanted in the rabbit calvaria in surgical critical size (2cm x 1cm) bone defects. The bone neoformation was analyzed 15, 30 and 60 days postsurgery and was made through radiographic, histological and electron spin resonance analyses (ESR). The last technique was used for complementary study of the bone mineralization. The histological results showed that the fraction of mature bone in the group treated with Latex membrane was higher than the ones of control group at 15 and 60 days post-surgery (P<0.05) and to the ones of group treated with PTFE in all periods of study (P<0.05). ESR results also demonstrate higher mineralization degree in the Latex s group in comparison with the others groups.